Perancangan Platform Digital dalam Efektifitas Administrasi Pembelajaran Dwibahasa di MI Nurul Falah - Dzaky Naufal Abiyyu; Yasin Efendi; Rikaro Ramadi; Mahbubul Wathoni; Sari Palestina (MES Bogor, 2026)
The integration of administration and learning in madrasas still faces obstacles, including at MI Nurul Falah Rawa Mekar Jaya, where administrative management and English and Arabic language learning have not been optimal. This study aims to develop a website-based digital platform capable of integrating these two aspects to improve the efficiency and quality of learning. The study used the Research and Development (R&D) method with the ADDIE model through the stages of analysis, design, development, implementation, and evaluation, involving teachers and 30 fifth-grade students as trial subjects. The research instrument was a validation questionnaire from media experts, material experts, and student responses. The results showed that the media expert validation was 72.5% (valid), material experts 91% (very valid), and student responses 86.25% (very practical). These findings confirm that the developed digital platform is not only feasible to use but also effective in improving student learning outcomes while simplifying madrasah administration management, thus having implications for improving the quality of technology-based education in the madrasah environment.